EXPLORING THE IMPACTS OF FINANCIAL FAILURE RISK ON SUSTAINABLE GROWTH POLICIES: EVIDENCE FROM THE BIST SUSTAINABILITY INDEX COMPANIES - Guzyurdu, Fatih; Yaman, Serdar (Economic And Financial Research Assoc - Efad, 2024)
This study investigates the impacts of financial failure risk on firms' sustainable growth policies using econometric analysis and aims to identify suitable financial failure models for the sustainable growth policies developing process. The study covers data from 38 non-financial firms listed in the Borsa Istanbul Sustainability Index (XUSRD) for 20102022. Sustainable growth is calculated by Higgins's (1977) sustainable growth rate (HSGR), while financial failure risks are assessed through Altman's (1983) Z'-score, Springate (1978) S-score, Taffler (1983) T-score, Fulmer et al. (1984) H-score and Legault (1987) CA-score models. The econometric approach employs a five-stage panel data methodology, including the pre-tests of multi-collinearity, cross-sectional dependency, slope homogeneity, stationarity, autocorrelation, and heteroskedasticity. Panel regression results reveal positive relationships between financial success and sustainable growth. However, the statistical significance of these relationships varies across different financial failure models. The effects of T and H-scores are statistically significant, whereas Z', S, and CA-scores do not exhibit statistically significant effects. Consequently, the findings suggest that T and H-score models should be prioritized in sustainable growth policy development.
Keywords: Sustainable Growth; Financial Failure Risk; BIST Sustainability Index; Panel Data Analysis